English proficiency barriers in Brazil: Communication challenges among international students and professionals - Olajide Owoyomi, Femi (Journal of International Students, 2025)
This study examines the challenges of English language proficiency faced by international students and professionals living in Brazil, highlighting the communication barriers that hinder academic, professional, and social integration. Using survey data collected from 200 participants in São José dos Campos—including primary school learners, university science students, hospital staff, and visiting scholars—the research investigates English proficiency levels, language-learning attitudes, and daily communication experiences across diverse demographic groups. Findings show that 80% of respondents reported having no English proficiency, and among the remaining 20%, only 15% expressed confidence in their skills. For international students and professionals, limited English proficiency in the surrounding community created substantial challenges when navigating daily life, accessing services, socializing, and seeking assistance. These barriers were most acute during the first year of residence, when limited Portuguese proficiency further compounded communication difficulties.